Unraveling Cults in West Java: A Socio-Legal Analysis of Teachings, Spread, and Human Rights Implications - Ahmad Ali Nurdin; Adon Nasrullah Jamaludin (UIN Sunan Gunung Djati, 2024)
This article investigates the phenomenon of cults in West Java, a province with the highest number of cult cases in Indonesia. Based on data from the Indonesian Ulema Council of West Java, the province hosts 144 cults. This study focuses on seven regencies: Bandung Regency, West Bandung Regency, Garut Regency, Tasikmalaya Regency, Ciamis Regency, Cirebon Regency, and Cimahi City, examining the distinct socio-demographic characteristics of these regions regarding teachings, spreading patterns, and the vulnerabilities that lead individuals to join cults. The research explores the legal responses and human rights challenges in managing and mitigating the influence of these cults, particularly in rural, economically disadvantaged, and low-education areas. The article argues that cults often thrive in these communities due to the promise of peace and solutions to life's challenges, raising significant concerns regarding the protection of vulnerable populations and the enforcement of legal and human rights standards.